Morphology and genitalia characters of Nadrana Baly, 1865 (Coleoptera: Chrysomelidae: Galerucinae) from Sundaland - Zulfadli M.,; Izfa R.H.,; Alia R.A., (Penerbit Universiti Kebangsaan Malaysia, 2015)
Taxonomic study of genus Nadrana (Coleoptera: Chrysomelidae: Galerucinae) was carried out using 159 specimens from the existing collections in the Centre for Insect Systematics (CIS), UKM and other repositories namely The Natural History Museum, London (BMNH), Collection of Jan Bezdìk, Bruno (CJB) and Swedish Museum of Natural History Stockholm (NHRS). From this study, the total of seven species listed in the genus remained, and became valid species within the arrangement of the genus. There was no major difference in the total body size, antenna, elytra and pronotum for all species; only colour variations were detected in those species. The genitalic characters particularly for each species consistenly characterized within the species in the genus, and presented for the first time in such publication. A total of seven valid species of Nadrana, and their redescription of morphological characters, as well genitalic characters and distribution are presented.This study proved that all species remained under this genus and need not to be transferred to any other genus; thus answering the question from Wilcox (1973) about the taxonomic status of Nadrana.